2018
DOI: 10.1089/ars.2017.7218
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Mediated Tumor Growth Inhibition Is Significantly Enhanced with Redox-Active Compounds That Cycle with Ascorbate

Abstract: The interplay between the accumulation of cationic MnPs and their potency as catalysts for oxidation of Asc, protein cysteines, and GSH controls the magnitude of their anticancer therapeutic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(95 citation statements)
references
References 64 publications
3
88
0
Order By: Relevance
“…While MnTnHex-2-PyP 5+ is a potent SOD mimetic, most recent studies point to its role and role of its porphyrin analogs (MnTE-2-PyP 5+ and MnTnBuOE-2-PyP 5+ ) in the modification of the activity of transcription factors including nuclear factor kappa B (NF-κB) and nuclear factor E2-related factor 2 (Nrf2) [ 22 , 43 , 44 , 45 , 46 ] and different mitogen-activated protein kinases, such as extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), protein kinase B (AKT) and p38 mitogen-activated protein kinase (p38-MAPK) [ 8 , 45 , 47 ]. Several studies provided evidence that this and other potent cationic porphyrin-based SOD mimics (such as MnTE-2-PyP 5+ and MnTnBuOE-2-PyP 5+ ) modify protein cysteines of transcription factors [ 44 , 45 , 46 ], MAPK, and protein phosphatase 2A through their S-glutathionylation, thereby modifying their activities [ 45 , 47 ]. We have provided the evidence and the mechanistic basis that the SOD-like potency of Mn porphyrins is proportional to their ability to S -glutathionylate cysteines of proteins [ 6 , 29 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…While MnTnHex-2-PyP 5+ is a potent SOD mimetic, most recent studies point to its role and role of its porphyrin analogs (MnTE-2-PyP 5+ and MnTnBuOE-2-PyP 5+ ) in the modification of the activity of transcription factors including nuclear factor kappa B (NF-κB) and nuclear factor E2-related factor 2 (Nrf2) [ 22 , 43 , 44 , 45 , 46 ] and different mitogen-activated protein kinases, such as extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), protein kinase B (AKT) and p38 mitogen-activated protein kinase (p38-MAPK) [ 8 , 45 , 47 ]. Several studies provided evidence that this and other potent cationic porphyrin-based SOD mimics (such as MnTE-2-PyP 5+ and MnTnBuOE-2-PyP 5+ ) modify protein cysteines of transcription factors [ 44 , 45 , 46 ], MAPK, and protein phosphatase 2A through their S-glutathionylation, thereby modifying their activities [ 45 , 47 ]. We have provided the evidence and the mechanistic basis that the SOD-like potency of Mn porphyrins is proportional to their ability to S -glutathionylate cysteines of proteins [ 6 , 29 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…A well known therapeutic attribute of MnPs is their ability to protect healthy cells and increase susceptibility of malignant cells to radiation therapy. This process has been attributed in part to increased H 2 O 2 which, in a process catalyzed by MnP, oxidizes signaling proteins such as NFκB [4,10,31]. Our results suggest that persulfides produced by MnP oxidation of H 2 S could have a similar effect with the added bonus of direct oxidant scavenging by persulfides.…”
Section: Antioxidant Function Of Mnp-generated Polysulfidesmentioning
confidence: 64%
“…As shown in Figure 6A,B, MnTE decreased H 2 S and increased polysulfides in both cell lines consistent with previous observations (cf. Figures 1 and 5 The biological actions of MnPs are thought to be due to redox cycling where oxidized Mn(III)P is reduced by a reductant such as ascorbic acid (AA) and then re-oxidized by oxygen which generates superoxide [4,[8][9][10]. The superoxide then spontaneously (or catalyzed by SOD or MnPs if present) dismutes to form peroxide and oxygen with the ultimate biological effects exerted by the peroxide.…”
Section: Effects Of Ascorbic Acid On Mnte Oxidation Of H 2 S In Hek Amentioning
confidence: 99%
“…Efforts have been made in order to develop methodologies to assess tissue and subcellular distributions of MnP. One of the analytical methods reported involves subcellular fractionation, substitution of the porphyrin Mn(II) site with Zn(II), followed by fluorimetric detection and LC-MS/MS quantification (57)(58)(59). Previous studies on cell incorporation, have observed the effect of MnP on SOD-deficient bacteria and yeast, which grow very poorly in the presence of oxygen.…”
Section: Introductionmentioning
confidence: 99%